Irradiation modification of epoxidized natural rubber/ethylene vinyl acetate/carbon nanotubes nanocomposites - Mohamed Yatim, Norazlina; Yusof, Faridah; Ratnam, Chantara Thevy; Sopyan, Iis (Trans Tech Publications, Switzerland, 2012)
The effect of irradiation on the mechanical properties of Epoxidized Natural Rubber/Ethylene Vinyl Acetate/Carbon Nanotubes (ENR/EVA/CNTs) nanocomposites were investigated. CNTs at various amount (2, 3, 4 and 6 wt%) were incorporated into ENR50 by solvent casting method. The ENR/CNTs were then blended with EVA by mixing in a Brabender Plasticoder at 120°C. Next, the samples were irradiated by using electron beam with 3 MeV electron beam machine in a dose range of 50 to 200 kGy. The mechanical properties such as tensile strength (Ts), modulus at 100% elongation (M100), elongation at break (Eb) and hardness of reinforced ENR/EVA/CNTs nanocomposites were studied as a function of radiation dose. It was found that, the Ts and M100 has increased almost 2 times compared to the nanocomposites without irradiation up to 150 kGy dose of radiation, and a downward trend thereafter. Gel fraction further confirmed the powerful energy of electron beam radiation result in irradiation-induced crosslinking and further enhanced mechanical properties of the nanocomposites.